SISTEM KENDALI TEKANAN UDARA PADA KOMPRESOR DENGAN PENGATURAN KECEPATAN MOTOR 3 FASA - Setiawan, Muhamad Aji; Riyanto, Indra (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
The purpose of this final project is to control air pressure (pressure) so that it can be controlled using PI control by adjusting the motor speed of 3 phase. So that it can be applied directly to the painting industry. In this final project discussed about the Air Pressure Control System in Compressors with 3 Phase Motor Speed Settings. The method used in this study uses Proportional, Integral (PI) controllers, control methods and settings to obtain Kp and Ki control parameters based on the Trial And Error method. Inverter with Unidrive M200-022 00075 type 1.5 kW base 0.75 kW 100-400 VAC as controlling current and air pressure (pressure). Arduino Mega 2560 microcontroller as the main control for processing PID control algorithm calculations. The air pressure sensor used by DC 5V 0-174 Psi / 1.2MPa pressure transmitter detects the air pressure affixed to the 3-phase compressor engine body. One jaguar piston compressor unit as a machine for processing compressed air. The 3 phase synchronous motor 220v / 380v 2HP as the piston driving motor on the compressor. Tests were carried out using 3 phase synchronous motor 2 HP and carried out using load and no load, with a pressure setpoint of 6 bar. In1 testing the overall PI parameters used can produce a pressure at steady state 5.89 bar from a setpoint of 6 bars, at a value of kp = 250 and ki = 100 with a set time of 113.6 seconds.